Physical Activity for the Treatment of Adolescent Depression: A Systematic Review and Meta-Analysis - Oberste, Max; Medele, Marie; Javelle, Florian; Lioba Wunram, Heidrun; Walter, Daniel; Bloch, Wilhelm; Bender, Stephan; Fricke, Oliver; Joisten, Niklas; Walzik, David; Großheinrich, Nicola; Zimmer, Philipp (Frontiers in Physiology, 2020)
Background: A noticeable proportion of adolescents with depression does not respond to guideline recommended treatment options. This systematic review and meta-analysis investigated the effectiveness of physical activity as alternative or complementary treatment for adolescents with depression. It was further examined what characteristics of the physical activity treatment, are most effective to reduce symptoms in adolescents with depression, and what role methodological shortcomings of existing research play. Methods: Medline, PsycINFO, SPORTDiscus, ProQuest, and CENTRAL were searched for eligible records. Effect size estimates were pooled applying random-effects model. Potential moderation of physical activity characteristics (intensity, type, context, and timeframe), and methodological features (type of control group, diagnostic tool to identify depression at baseline) was investigated using subgroups-analyses and meta-regressions. The certainty of evidence was assessed by the GRADE approach. Primary outcome was the anti-depressant effect of physical activity after termination of treatment. As secondary outputs, we assessed the sustainability of effects and the acceptability of physical activity treatments. We included 10 studies in qualitative synthesis. Nine studies (N=431) were included in quantitative synthesis. Results: A moderate, significant anti-depressant effect of physical activity was revealed (Hedges’ g=-.47, 95% CI=-.71 to -.24). Heterogeneity was small (т2=.0313, I2=27%, p=.18). However, certainty of evidence had to be downgraded to low because included studies showed serious methodological limitations. Moderator analyses revealed that session intensity significantly moderated the anti-depressant effect of physical activity. Moreover, we found noticeably smaller effect sizes in studies that used active control treatments, compared to studies that used passive control treatments. We found indications that the anti-depressant effects further evolved after treatment termination. There was no significant difference between dropout risk in physical activity and control groups. Conclusions: This review suggests that physical activity is effective to treat depression in adolescents. Physical activity sessions should be at least moderately intense to be effective. Furthermore, our results suggest that physical activity treatments are well accepted. However, low methodological quality and potential placebo effects in included studies might have led to effect overestimation. Therefore, we need more studies on higher methodological level to increase the strength of recommendation for physical activity treatments in adolescents with depression.